AN ESTIMATION OF THE HYDRODYNAMIC FLOW FIELD (HDFF) AROUND A SPHERE THROUGH CFD AND EXPERIMENT (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
In the presented study is made a numerical modelling of the hydrodynamic flow field (HDFF) around a sphere. Numerical modelling has been made using the software ANSYS Workbench and the calculation of the hydrodynamic flow field (HDFF) around a sphere was implemented using the solver ANSYS Fluent. The analysis of HDFF around the sphere has realized using Finite Element Method (FEM) available in the ANSYS Fluent environment. The HDFF has examined around the sphere at a given horizon using the real flow, the fluid is water. The obtained numerical results for velocities and pressures around the sphere have compared to actual experimental data, [1]. The aim of the presented study is to propose a numerical approach that can give adequate assessment of HDFF in a real turbulent flow around a sphere immersed in water using modern computational methods as CFD Fluent and validation of these results with real experimental data.